Pemanfaatan Aplikasi Paint Untuk Pengenalan Teknologi Informasi Pada Siswa SD Negeri Air Lesing - Aktavera, Beni; Intan, Bunga; Armanto, Armanto; Nurdiansyah, Deni; wijaya, harma oktafia lingga; Basmansyah, Attaya Rifki; Purwanti, Devi (Lembaga Dongan Dosen, 2025)
Air Lesing State Elementary School in Musi Rawas Regency is one of the primary schools that plays an important role in providing basic education for children in the region. As an educational institution that is committed to shaping character and providing basic knowledge, SD Negeri Air Lesing strives to provide a safe, comfortable, and conducive learning environment for its students. In the midst of the development of the times and the need for digital literacy, SD Negeri Air Lesing has also begun to strive to introduce information technology in learning. Although it is located in an area that may not be as developed as urban, it strives to provide equal access to education, as well as prepare students to be ready for the challenges of the modern era. This information technology learning is not only aimed at introducing tools and software to students, but also to build logical and critical thinking skills, and develop creativity. To introduce information technology to SD Negeri Air Lesing students through one of the drawing applications, namely the paint application. The problem that exists at SD Negeri Air Lesing has never learned to use technology so that technology for SD Negeri Air Lesing, they are still very unfamiliar, let alone the use of applications for drawing such as paint applications, They are still very unfamiliar, especially the use of applications for drawing such as the Paint application, so it is hoped that students can get to know and be able to implement the Paint application for drawing. This service was carried out directly, with the participation of 35 students, producing digital drawing artworks using the paint application. And 95% of students can already use it